Analysis Of The Foundation Of Customer Loyalty: The Influence Of Service Quality, Brand Image And Trust On Customer Loyalty Of Bank Syariah Indonesia KC Medan S. Parman 2025 - Caesario, Muhammad Arief; Agustin, Roro Rian (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of service quality, brand image, and trust on customer loyalty with trust as an intervening variable in Bank Syariah Indonesia KC Medan S. Parman in 2025. The research uses a quantitative approach with a survey method to 200 customers through purposive sampling techniques. The data was analyzed using Structural Equation Modeling (SEM) with the help of AMOS 26 software. The results showed that service quality and brand image had a positive and significant effect on customer trust with a path coefficient value of 0.427 and 0.385 (p<0.05), respectively. Trust was proven to mediate the relationship between service quality and brand image on customer loyalty with a total influence of 0.519 and 0.462. These findings make a theoretical and practical contribution to the development of Islamic banking marketing strategies in increasing customer loyalty in today's digital era.